Evaluation of Fertilizer Applicator for Direct Seeding - Sharma, ISRP; Murthy, G.R.K; Hemasankari, P; Kumar, R Mahendra (Journal of Agricultural Engineering, 2008)
Seeding with simultaneous application of fertilizer is highly productive and efficient in enhancing fertilizer use efficiency in rice. The present study aimed to develop a fertilizer applicator as an attachment to the drum seeder. The modified drum seeder with fertilizer applicator consisted of a rotor having cups, which can deliver 46 kg N/ha in total. The fertilizer box is fixed in between the two drums of the row seeder. At a time 4 rows of sprouted seed could be sown. This unit could be used for basal and second split of urea application, where as the third split is done by usual way of broadcasting. The fertilizer applicator was evaluated during rabi 05-06 and kharif 05-06. The treatments included: direct seeding with row seeder, with fertilizer applicator and with out N taken as control. Fertilizer use efficiency of 15.15 and 21.5 kg grain per kg of N (Agronomical efficiency of N) was obtained for row seeder and fertilizer applicator respectively after deducting zero N yield. Similarly, for Rabi, these corresponding figures were 18.96 and 27.12 kg grain per kg of N. The percentage increase of fertilizer use efficiency in case of Kharif and Rabi works out to be 41.57 and 43.15 respectively using fertilizer applicator.